Actions to reduce gender gaps in academia: Insights from the Chilean experience - Suárez Amaya, Wendolin; Ganga-Contreras, Francisco (Revista de Ciencias Sociales, 2022)
Gender perspective in universities has become a topic of extreme relevance in the management and governance of these educational entities since it seeks to contribute to the construction of a more just society where men and women have the same rights and opportunities in the educational, economic, and labor spheres. From this perspective, this work seeks to characterize the actions being carried out in the area of gender, which are being put into practice in Chilean state universities through a documentary review that included scientific articles and various institutional documents. Generally, it was detected that there is a direct involvement from the strategic level, evidenced by the creation of a new institutional framework. It is concluded that universities face the challenge of adapting their forms of government and promoting the required cultural change, according to the particular needs of each institution.